Evaluation of the Quality Indicators in Laboratories at National AIDS Research Institute, Pune, India - Sangeeta Kulkarni; Sachin Kale; Urmila Ghodke; Arun Risbud; Smita Kulkarni (Medsci Publications, 2017)
Introduction: Quality indicators in a clinical laboratory are considered as useful tools for continual improvement of the laboratory services. Aim: The aim of this study was to assess timely performance of the NARI service laboratories in three phases of testing - pre-analytical, analytical and post-analytical, in an effort to improve their performance. Methodology: The study included an assessment of different quality indicators from six laboratories - Clinical Biochemistry, Hematology, Serology, Microbiology, Virology and Immunology at the NARI central laboratory which provide service for the patient care. Results: Data obtained from a total of 39139 clinical samples collected over a period of two years was used in the study. The overall error rate was found to be 2.72%. The commonly observed indicators were revision of the laboratory requisition form (0.49%) and sample rejection (0.31%) during the pre-analytical phase, equipment breakdown (0.12%) and failure of the controls (0.03%) during the analytical phase, turnaround time (1.55%) and revision of the report form (0.15%) during the post- analytical phase. Conclusions: Quality indicators are important tools in improving the quality system in a clinical laboratory and patient care.